Rational development of liposomal hydrogels: A strategy for topical vaginal antiretroviral drug delivery in the context of HIV prevention - Faria, M (2019)
HIV/AIDS stands as a global burden, and vaginal microbicides constitute a promising strategy for topical pre-exposure prophylaxis. Preceding the development of a microbicide containing tenofovir disoproxil fumarate (TDF) and emtricitabine (FTC), in silico and in vitro studies were performed to evaluate the physicochemical characteristics of both drugs, and to study their biophysical impact in lipid model systems. Results from these pre-formulation studies defined hydrogels as adequate vehicles to incorporate TDF-loaded liposomes and FTC. After studying interactions with mucin, zwitterionic liposomes with a mean diameter of 134 ± 13 nm, an encapsulation TDF efficiency of approximately 84%, and a transition temperature of 41 °C were selected. The chosen liposomal formulation was non-cytotoxic to HEC-1-A and CaSki cells, and was able to favor TDF permeation across polysulfone membranes (Jss = 9.9 ug.cm-2,h-1). After the incorporation of TDF-loaded liposomes and FTC in carbomer hydrogels, the drug release profile was sustained over time, reaching around 60% for both drugs within 3-6 h, and best fitting the Weibull model. Moreover, liposomal hydrogels featured pseudoplastic profiles that were deemed suitable for topical application. Overall, the proposed liposomal hydrogels may constitute a promising formulation for the vaginal co-delivery of TDF/FTC.